Beyond Mitigation : Quantifying the Development Benefits of Carbon Pricing - Partnership for Market Readiness (Washington, DC: World Bank, 2021)
Carbon pricing can reduce emissions cost-effectively, and it can also generate a number of other benefits. This guide provides an overview of these benefits to help policy makers advance a variety of sustainable development objectives in their own countries and around the world. Carbon prices are broadly recognized as necessary for correcting market failures that arise from pollution externalities, because the prices paid for using fossil fuels do not come close to compensating society for the costs that greenhouse gas (GHG) emissions impose on society. Where there is a divergence between (externality-based) social costs and private values, carbon pricing is an essential environmental policy tool. The purpose of this guide is to help policy makers identify and measure carbon-pricing benefits. In particular, it provides insights into how to incorporate benefits into computable general equilibrium (CGE) modeling.